The development of speed, agility and coordination in young football players of the U12 category - Mihai ȘANDRA; Gheorghe Codruț BULZ; Marius Alin MARINĂU (Editura Universităţii din Oradea, 2022)
Physical training has been given special attention in recent years in the world of high-performance sports in general and in football in particular. In the context where we are witnessing a standardization of technical-tactical values, many times the level of physical training is what makes it possible to tie the teams. Sports performance has progressed a lot, we meet more and more often performances that in the past seemed impossible to achieve, but currently this fact is possible thanks to the accumulation of several factors such as: streamlining the selection process, modernizing the materials and facilities used in training and competition, the improvement of training methodologies, better trained specialists and the direct involvement of science in the sports training process. Thus, the current study proposes the development and application of training cycles centered on the development of speed, agility and coordination in children under 12 years old who practice football. To evaluate the results, a battery of tests was prepared that includes specific evaluations for each motor quality considered. The results show that the selection of means and methods aimed at developing speed, agility and coordination/skill are essential in the training process of young footballers, and the applied training cycle gives very good results for the analyzed age group. All the athletes improved their results between the initial and the final testing period, which indicates a maximum effectiveness of the training.